Reconstruction of Mebuug-Buugan Tradition as Revitalization of Local Wisdom in Kedonganan Traditional Village, Kuta District, Badung Regency - I Made Sudarsana; Agung Adi; Irawine Rizky Wahyu Kusuma (Sociological Jurisprudence Journal, 2021)
This article aims to explore as well as explain the causes and implications of the reconstruction of the Mabuug-Buugan tradition in the Kedonganan Traditional Village. Mebuug –Buugan is one of the important traditions in the celebration of Nyepi which is owned by the Kedonganan Indigenous people. But over time, this tradition has not been implemented for approximately 60 years, based on information, the last Mabuug-Buugan was carried out in 1965. In that period until 2012, the stories and practices of Mabuug-Buugan were almost inaudible, especially when they were practiced. In the era of 2014, the practice of mabuug-buugan was reconstructed with various forms of discourse as an effort to revitalize the local wisdom of the indigenous people of Kedonganan. This research uses a descriptive approach, the theory as a basis is semiotics. Data were collected using observation techniques, in-depth interviews and documentation. Data analysis using interactive models and data triangulation. Based on the analysis carried out, there are several causes for the reconstruction carried out, namely; a) the problem of the identity of the cultural traditions of the Kedonganan Indigenous people; b) environmental issues; c) tourism modernization. Meanwhile, the implications of the reconstruction of the Mabuug-Buugan tradition are; a) myth renewal: from games to Nyepi theology and philosophy; b) The occurrence of mangrove environmental preservation; c) annual tourism attractions.